The linguistics of lying and other essays - Weinrich, Harald (Literary conjugations., 2005)
"Can language hide thoughts? This question was answered by Harald Weinrich in this volume's title essay, first published in 1966 as Linguistik der Luge. Weinrich's essay, now in its sixth printing in Germany, is presented here for the first time in English, with an updated preface by the author. Additional essays selected by him complement "The Linguistics of Lying" in their focus on real and false representations in literature and in life."